SPECIFICS OF POWER CONSUMPTION OF THE RUSSIAN ECONOMY - Zuber Musovich Kertbiev (Statistika i Èkonomika, 2016)
Article is devoted to research of structure of the used fuel and energy resources inthe Russian economy on ﬁ nal consumption. It is shown that the domestic economy is one of the most power-intensiveeconomies of the world now. Thus, process of consumption of fuel and energyresources underwent serious structural changes that was followed by change ofa share of speciﬁc sectors in consumptiontotal volume.